A multidimensional examination of the acculturation and psychological functioning of a sample of immigrant Chinese mothers in the US - Tahseen, Madiha (Int J Behav Dev, 2012)
The present research used the cluster analysis method to examine the acculturation of immigrant Chinese mothers (ICMs), and the demographic characteristics and psychological functioning associated with each acculturation style. The sample was comprised of 83 first-generation ICMs of preschool children residing in Maryland, Unites States (US). Cluster analysis revealed four acculturation styles: psychologically-behaviorally integrated; psychologically-behaviorally assimilated; psychologically-behaviorally undifferentiated; and psychologically-behaviorally separated. Assimilated mothers were the youngest at immigration and had resided in the US for the longest time. Separated mothers were older at immigration, resided in the US for a shorter time, were less educated, and had lower psychological functioning than mothers in the other clusters. However, there were no differences in demographic characteristics and psychological functioning between psychologically-behaviorally integrated and psychologically-behaviorally undifferentiated clusters. The importance of simultaneously assessing various cultural orientations and components of acculturation was highlighted.